Neural mechanisms of attention become more specialised during infancy: Insights from combined eye tracking and EEG. Issue 2 (15th December 2016) - Kulke, Louisa; Atkinson, Janette; Braddick, Oliver
Abstract: The Fixation Shift Paradigm (FSP) measures infants' ability to shift gaze from a central fixation stimulus to a peripheral target (e.g. Hood & Atkinson, 1993: Infant Behavior and Development, 16(4), 405–422). Cortical maturation has been suggested as crucial for the developing ability to shift attention. This study investigated the development of neural mechanisms by combining EEG with simultaneous eye tracking during FSP testing, in typically developing infants aged between 1 and 8 months. The most prominent neural response was a frontal positivity which occurred only in the hemisphere contralateral to the target in the youngest infants but became more ipsilateral with age. This changing lateralisation was associated with improving ability to shift attention (decreasing saccade latencies and fewer 'sticky fixations'—failures to disengage attention from the central target). These findings suggest that the lateralisation of neural responses develops during infancy, possibly due to developing intracortical connections, allowing infants to shift attention more efficiently. RESEARCH HIGHLIGHTS: Successful use of combined simultaneous remote eye tracking and EEG to measure infant attention shifts. Neural responses involved in attention shifts change in the first year of life. The lateralisation of EEG responses changes with age in the first year of life. Frontal cortex is involved in attention shifts from around 2 months of age.